Relações entre configurações de poder, prazer e sofrimento e intenção de rotatividade : estudo de caso numa empresa de tele-atendimento - Pereira, Cynthya Coelho Prates (2006)
The objective of this study was to investigate the variables power configurations and pain and pleasure at work as predictors of turnover intention with call center operators. To investigate these relations, a case study in a great contact center company was carried through with 286 participants who answered consistent and validated scales: Scale of Organizational Power; Scale of Pain and pleasure and Scale of Turnover Intention. Descriptive analyses and multiple regressions have been, then, carried through, considering the measure of Turnover Intention as a dependent variable. The results had indicated that the call center operators fell more pleasure than pain at work and the power configuration more significant were closed system, missionary and autocracy. The power configurations are slightly predicted for turnover intention, explaining only 9% of the total variance. However, the power configuration missionary, closed system and autocracy, were strong predictors for the four factors of pleasuresuffering. The three configuration of organizational power explained 26% of the total variance in the prediction of Gratification; 28 % in the prediction of Liberty and 14% in the prediction of Displeased. Pleasure and suffering are strong and significant predictors of turnover intention, explaining 43% of total variance. The results had indicated that the principal hypothesis at this study was validated. The results were discussed and they were comparing them with the ones of other studies.